Gluten-free Buckwheat Kvass with Aromatic Raw Materials - Tanashkina T.; Peregoedova A.; Semenyuta A.; Boyarova M. (Техника и технология пищевых производств)
Introduction. The production of gluten-free food products, including alcohol-free beverages, is an urgent task for Russian food industry. Buckwheat malt has a great raw material potential, because it consists rutin, which can give the final product some useful functional properties. Aromatic raw materials improve the sensory characteristics of beverages and increase their nutritional value. Study objects and methods. Kvass is a traditional Russian bread juice. To prepare gluten-free kvass, we used light and scalding buckwheat malt and water infusions of barberry, juniper, leaves of garden currant, and lemon balm grass. The wort was prepared by infusion and fermented with bottom beer yeast Saflager W-34/70. Then it was blended with infusions of plant materials. Sensory and physical and chemical properties of kvass were determined by standard methods. Antioxidant activity of the beverages was assessed by using DPPH radical scavenging method. Results and discussion. All samples met the state standard requirements for kvass by sensory, physical, and chemical characteristics. The drinks obtained from the scalding malt were well-fermented and achieved better tasting ratings compared to those from the light malt. The control sample, which contained no aromatic raw materials, received the lowest scores for taste and aroma. The kvass blended with infusions of barberry and garden currant had the best results. The infusions increased the shelf life of the kvass from 7 days (control) to 12 (barberry), 14 (juniper), and 16 (currant). All samples of kvass demonstrated antioxidant activity, the beverage with infusion of garden currant leaves showing the best results (≤ 80%). Antiradical activity was established for the samples blended with barberry and currant infusions. Conclusion. light and scalding buckwheat malt can be used to prepare gluten-free kvass. Blending buckwheat kvass with infusions of aromatic raw materials increased the shelf life of the beverages, improved their taste, aroma, and antioxidant activity (except the sample with infusions of juniper), and gave them antiradical properties.